2002
DOI: 10.1111/1468-0432.00165
|View full text |Cite
|
Sign up to set email alerts
|

Gender and New Public Management: Reconstituting Academic Subjectivities

Abstract: This article is located within the context of British Higher Education. It examines the ‘radical reforms’ of New Public Management (NPM) (marketization and managerialism) in the management of university organizations. The article has two main aims. First, to explore the extent to which NPM initiatives have influenced individual women academics’s day–to–day experiences of the gendered academy and their professional identities. Second, to understand individuals’ active responses to NPM to develop theorizing of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
193
0
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(205 citation statements)
references
References 35 publications
(78 reference statements)
5
193
0
7
Order By: Relevance
“…Authors such as Raddon (2002) and Haynes and Fearfull (2008), among others, have empirically explored the institutional allocation of administrative and research activities in order to highlight the production and reproduction of gendered roles and identities within the academy. They have reported, similarly to our interviewees, that many academic women are under pressure to accept a heavier teaching load and more pastoral care than their male colleagues who can focus more on research and external networking (see also Davies, 2002 andAcker andFeuerverger, 1996). This results in a reduction of research time and therefore of research publications (Brooks, 2001).…”
Section: Challenging Subjectivities: Resisting Gendered Stereotypessupporting
confidence: 54%
See 1 more Smart Citation
“…Authors such as Raddon (2002) and Haynes and Fearfull (2008), among others, have empirically explored the institutional allocation of administrative and research activities in order to highlight the production and reproduction of gendered roles and identities within the academy. They have reported, similarly to our interviewees, that many academic women are under pressure to accept a heavier teaching load and more pastoral care than their male colleagues who can focus more on research and external networking (see also Davies, 2002 andAcker andFeuerverger, 1996). This results in a reduction of research time and therefore of research publications (Brooks, 2001).…”
Section: Challenging Subjectivities: Resisting Gendered Stereotypessupporting
confidence: 54%
“…Authors (e.g. Park, 1996;Thomas and Davies, 2002;Priola, 2007) have observed the tendency for these relations to disadvantage women in both their research and managerial careers. In such institutionalised workplaces initiating and sustaining change is particularly difficult and problematic because the persistence of gendered structures and processes is partly attributed to institutional configurations that legitimise and ascribe neutrality to these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus women wanted 'to achieve in their own right and through their ability', but they suggested that this was 'not just naivete', and that it reflected a 'deep repugnance for academic politics (quoting Aisenberg and Harrington, 1988). In the present study, some men also stressed women's greater passivity in terms of career planning and/or a lack of ambition in an increasingly managerialist context where undergraduate teaching was seen as low status work to be undertaken by 'secondary, 'solid troupers', rather than academics at the cutting edge of knowledge production' (Thomas and Davies, 2002: Grummell et al (2008: 13) noted that in their study, women were more likely than men to have no children. In the present study, a number of the female interviewees (but no men) spontaneously referred to the fact that they had no children.…”
Section: (Professor Garry Burke); 'Women Don't Think They Are Good Enmentioning
confidence: 53%
“…However, it would be erroneous to represent women academics in terms of victim or angel narratives and to ignore hierarchies and power relations among women. Equally, unitary or deterministic representations of women and men do not contribute to knowledge about the complexity and multiplicity of experiences (Thomas and Davies, 2002). I would argue that we need a theory of privilege in higher education, rather than simply a focus on disadvantage.…”
Section: The Affective Domain: Being Judged and Found Wantingmentioning
confidence: 98%